Model Penafsiran Kisah oleh Muhammad Abduh dalam Al-Manar: Studi Kisah Adam pada Surah Al-Baqarah - Bustamam, Risman; Aisyah, Devy (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2020)
This paper aims to criticize Tafsir al-Manar, Muhammad Abduh's monumental work as a pioneer of modern interpretation, which criticizes classical interpretative works, which he considers to be too story oriented, then offers a method of interpreting stories that focuses on `ibrah narratives, although not maximally. This study is a research library, using a semantic perspective as a knife of analysis, through three approaches; interpretation, content analysis, and hermeneutics. This study found that Abduh had applied the method of interpretation of the verse of the story that he had conceived. From the perspective of semantic interpretation and study, Abduh interprets verse by verse, studies the meaning of lughah, and reviews balaghah, munasabah, which focuses on hida'i (hidayah) and intiqadi (critical studies), and does not use hadiths. That is, Abduh is consistent with the Salaf pattern in interpreting the story, namely positioning it as mutasyabihat, and holding to the principle; tanziih, tasliim, and tafwiidh, and anti-takwil.